The Impact of the Tips from Former Smokers® Campaign on Reducing Cigarette Smoking Relapse. (22nd November 2022) - Davis, Kevin; Murphy-Hoefer, Rebecca; Dutra, Lauren; King, Brian; Bradfield, Brian; Rodes, Robert; Beistle, Diane
Abstract : Evidence-based mass-reach health communication campaigns can increase tobacco cessation, use of cessation resources such as quitlines, and change tobacco-related social norms. These interventions have been associated with a lower likelihood of cigarette smoking relapse in studies conducted internationally; however, no studies have assessed this outcome for a national campaign in the United States. This study examined the relationship between Tips from Former Smokers® ( Tips® ) campaign exposure and the odds of cigarette smoking relapse among adults who formerly smoked. Using data from the 2014 to 2019 Tips longitudinal campaign surveys, we estimated first episode of relapse (versus remaining a former smoker) as a function of Tips gross rating points (GRPs, a measure of media exposure). Higher levels of Tips GRPs were associated with lower odds of relapse (aOR = 0.63, 95% CI: 0.50-0.78). These results suggest that the Tips campaign may reduce smoking relapse, in addition to the established effect of increasing smoking cessation. Former smokers can be considered a secondary target audience for smoking cessation mass media campaigns, and mass media campaigns could be considered a component of smoking relapse prevention efforts.